Analisis Pengaruh Pengungkapan Environmental, Social, and Governance (ESG) terhadap Nilai Perusahaan dengan Pendekatan Tobin’s Q: (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia) - Amanda Mechtildis Christiani; Sylvia Fettry Elvira Maratno (AKUNTANSI 45, 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) on firm value in mining companies listed on the Indonesia Stock Exchange for the 2021-2024 period. Firm value is proxied using Tobin’s Q, while profitability, proxied by return on assets (ROA), and firm size are used as control variables. This study uses a quantitative approach with a causal associative research type. Research data were obtained from annual reports and company desire reports. To reduce extreme data variations and improve the normality of data distribution, firm value and firm size variables were transformed into natural logarithm (LN) form. Data analysis was performed using multiple linear regression methods with the help of Jamovi software. The findings of this study indicate that profitability (ROA) has a positive and significant effect on firm value. On the other hand, ESG distribution and firm size do not show a significant effect on firm value. Simultaneously, ESG, ROA, and firm size have a significant effect on firm value with a contribution of 41.2%. The empirical findings of this study confirm that in the context of an emerging market like Indonesia, investors in the mining sector tend to prioritize company fundamentals, particularly profitability, over desirability or operational scale when assessing companies.